Respuesta :
Answer:
(a) 1168.78 N, (b) 932.93 N and (c) 757.95 N, approximately.
Explanation:
In general, let's suppose the elevator is moving upward with a constant acceleration [tex]a[/tex], then by applying Newton's second law on the person and writing for the normal force (which is the one the scale displays), we have
[tex]ma=\sum F\\ma=N-mg\\N=m(a+g).[/tex]
(a) [tex]a = 2.48 m/s^2[/tex]
[tex]N=95.1 kg\times\left(2.48\frac{m}{s^2}+9.81\frac{m}{s^2}\right)\\N=1168.779 N[/tex].
(b) [tex]a = 0 m/s^2[/tex]
[tex]N=95.1 kg\times\left(0\frac{m}{s^2}+9.81\frac{m}{s^2}\right)\\N=932.931 N[/tex].
(c) [tex]a = -1.84 m/s^2[/tex]
[tex]N=95.1 kg\times\left(-1.84\frac{m}{s^2}+9.81\frac{m}{s^2}\right)\\N=757.947 N[/tex].
Answer:
Explanation:
Mass of the person in elevator
M = 95.1kg
a. When the elevator is accelerating upward at 2.48m/s²
Fnet = ma
R — W = ma
R — mg = ma
R = ma+mg
R = m(a+g)
R = 95.1(2.48+9.81)
R = 95.1 × 12.2
R = 1168.78N
b. Elevator moving upward at a constant speed
This means that it is not accelerating. Therefore, the acceleration is zero
Fnet = ma
a = 0
Fnet = 0
R - W = 0
R = W
R = mg
R = 95.1 × 9.81
R = 932.931 N.
c. Elevator accelerating downward at 1.84m/s².
Fnet = ma
Since it is downward, a is moving in -ve direction of y axis
R — W = -ma
R = W—ma
R = mg —ma
R = m(g-a)
R = 95.1(9.81—1.84)
R = 95.1 × 7.97
R = 757.947 N.